What is the Teaching Excellence Framework in the United Kingdom, and Will it Work? - Ashwin, Paul (International Higher Education, 2017)
In this article Ashwin discusses the Teaching Excellence Framework that is being introduced in England. He examines why it is being introduced, how it will work, whether it will meet its aims and how it might develop in the future.